Beyond the Arab Spring in North Africa - Křížek, Daniel; Záhořík, Jan (Lexington Books, 2017)
From revolution to disillusion : the story of Egyptian youths within the Arab Spring / Dina Abdelrahman -- Competing perspectives on women's rights before and after the Arab Spring : the view from Tunisia / Ola Raddaoui -- The legacy of Sidi Bouzid : overcoming spatial inequalities in Tunisia / Maximilian Benner -- Winter still for LGBT individuals in the Maghreb after the Arab Spring? / Ncube Gibson -- From Khaled Said to Moaz al-Kasasba : critical thoughts on the role of new media in the Arab uprisings / Zbyněk Tarant -- Regionalism in MENA in Arab Spring and post Arab Spring milieu : problems and prospects / Muhammad Atif Khan -- North African Arab Spring in the Czech dailies / Veronika Sobotková -- Ali Abd al-Raziq and the politics of secularism : breaking the Islamist-liberal impasse / Christian Donath -- Demotic legitimacy and modernization : a case for optimism about Islamic democracy / Alexander Maxwell
Includes bibliographical references and index
Keywords: Africa, North -- Social conditions -- 21st century; Aufsatzsammlung; Geschichte; Arabischer Frühling; Nordafrika